PENINGKATAN KETERAMPILAN KOMUNIKASI SISWA MELALUI MODEL PROBLEM-BASED LEARNING DALAM PEMBELAJARAN AGAMA BUDDHA - Ratnasari, Evi; Hariyanto; Dwiyono Putranto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the implementation of Problem-Based Learning (PBL) to enhance students’ communication skills in Buddhist Religious Education at SMA Negeri 1 Girimulyo, Indonesia. Using a Classroom Action Research (CAR) design, the research was conducted in two cycles involving three Buddhist students from Grade XI. The study employed observation, interviews, and documentation to collect qualitative and quantitative data, focusing on key indicators of communication skills such as effective expression, active listening, interpersonal interaction, and clarity. Findings from the first cycle indicated limited student participation, low self-confidence, and challenges in articulating ideas. After pedagogical refinements and full integration of the PBL model in the second cycle, student performance improved significantly. The average communication score rose from 65.67% in Cycle I to 73.44% in Cycle II. Students became more active in discussions, demonstrated increased confidence during presentations, and responded more effectively to their peers. The results demonstrate that PBL not only promotes student engagement but also fosters meaningful learning through culturally relevant content. This approach enables students to connect Buddhist values with real-world issues, enhancing both their cognitive and moral development. Therefore, PBL is a promising strategy for religious education, especially in minority contexts, offering a dynamic model that supports critical thinking, collaboration, and ethical reflection.